MICROMORPHOLOGICAL STUDY FOR POLLENS AND SEEDS FOR FIVE SPECIES BELONG TO BRASSICACEAE FAMILY IN IRAQ - T.A. AL-Sammariy; Z. A.Ismaeel; S.A.Aliwy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to investigate the micro-morphological characteristics of pollens and seeds for five species of the Brassicaceae family in Iraq belonging to the genus Lepidium, and species of Lepidium sativum L., L.ruderale L. , L.perfoliatum L., L.aucheri Boiss, and L.latifolium L. The characteristics of the pollen grains included the shape of the grain, the length of the equatorial and polar axis, the distance between the two grooves and the groove length , as well as the grain surface configuration. The seeds spherical in shape, while the other species were elongated in shape. As for the seeds, they were studied by the Dissect microscope and the scanning electron microscope (SEM), and all their morphological characteristics were studied the shape, dimensions (length and width), colors, as well as the presence of the mucous layer, that all the seeds of the species contained a mucous layer, but they varied in their thickness, and the surface configuration of the seed surface varied between zigzag reticulate, reticulate different shapes, pitted reticulate, and elongated reticulate.